Development of Simple Science Learning Media in the Form of Reaction Rate Tools for Effective Understanding of Teaching Materials - Zahara, Medi; Vebrianto, Rian (Balai Publikasi Indonesia, 2024)
Chemistry is one of the study materials in Natural Sciences (IPA) subjects which aims to provide knowledge to students in understanding chemistry learning concepts. One of them is the material on reaction rates, which is one of the studies in chemistry that really demands macroscopic, microscopic and symbolic aspects. This research is a type of analysis and development research which was carried out from April 24 to April 27 2019. The population involved in this research were all Tadris Science class B students with a total of 31 respondents. Reaction rate material in junior high school is still taught through the lecture method and by memorizing concepts without involving the microscopic aspects which will cause difficulties in understanding the concept of reaction rate meaningfully. Therefore, this research aims to utilize learning media which is closely related to improving the quality of learning which is expected to create a more meaningful learning experience, facilitate the process of interaction between students and teachers and students who are relevant anywhere, and enrich the students' learning experience. The results of this research are all questions for each validity have valid status, because the value of Rcount > Rtable is 0.355 and the result of the reliability coefficient of the content instrument is Ralpha = 0.621, the construct instrument is Ralpha = 0.675, the prediction instrument is Ralpha = 0.676, the concurrent instrument is Ralpha = 0.707, and the efficiency instrument is Ralpha = 0.610, apparently it has a